2020
DOI: 10.1136/bcr-2019-233020
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneousAspergillus fumigatusinfection in immunocompetent host

Abstract: Primary cutaneous aspergillosis (PCA) occurs through inoculation of fungal spores directly into the skin from the environment through disrupted skin such as in burns, surgery or penetrating trauma patients. Most cases reported in literature were in the immunocompromised, rarely in immunocompetent patients. The characteristic lesion of cutaneous aspergillosis is a black eschar on a red plaque, or nodule at the site of skin injury. The diagnosis of PCA can be made by identifying hyphal forms on routine H&E s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Patients meeting any of the following criteria for immunosuppression were selected: (1) tumor (organ and blood system); (2) solid-organ, stem cell, or bone marrow transplantation states; (3) autoimmune diseases with immunosuppressive therapy (more than 10 mg of prednisone or equivalent per day for at least 3 weeks or oral methotrexate, cyclosporine, azathioprine, or biological modifiers within 3 months); (4) poor diabetes control; (5) liver cirrhosis; (6) postoperative critical condition; and (7) burns ( McCann et al., 2004 ; Blanchard et al., 2020 ; Lindell et al., 2020 ; Mada et al., 2020 ; Barlas et al., 2021 ; Turkkan et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients meeting any of the following criteria for immunosuppression were selected: (1) tumor (organ and blood system); (2) solid-organ, stem cell, or bone marrow transplantation states; (3) autoimmune diseases with immunosuppressive therapy (more than 10 mg of prednisone or equivalent per day for at least 3 weeks or oral methotrexate, cyclosporine, azathioprine, or biological modifiers within 3 months); (4) poor diabetes control; (5) liver cirrhosis; (6) postoperative critical condition; and (7) burns ( McCann et al., 2004 ; Blanchard et al., 2020 ; Lindell et al., 2020 ; Mada et al., 2020 ; Barlas et al., 2021 ; Turkkan et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, typical immunosuppressive status includes patients with hematological diseases, tumor, oral immunosuppressive medications, solid-organ transplant, stem cell transplant, or bone marrow transplant, and atypical immunosuppressive status includes patients with diabetes mellitus, liver cirrhosis, and burns ( Mylotte and Tayara, 2000 ; Li et al., 2021 ; Willis et al., 2021 ). Studies revealed that immunosuppression could result from critical surgery as well ( Si et al., 2021 ), and sometimes postoperative patients are susceptible to infections caused by opportunistic pathogens ( Mada et al., 2020 ; Shipman et al., 2021 ). IS patients with infections may present with atypical signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Bloodstream infection is closely associated with high mortality in ICU. 5 Immunosuppressed people were vulnerable to severe infections because of ICU admission. The high mortality in immunosuppressive status was also caused by infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressed patients included the patients under immunosuppressive therapy (use of drugs like corticosteroids [prednisone equivalent > 20 mg/day] for at least 14 days, or methotrexate, cyclosporine, azathioprine, or biological modifiers within three months), posttransplantation includes solid-organ, stem cell, or bone marrow transplantation, cancer includes solid organ and hematological system tumors, burns, diabetes, liver cirrhosis, and critical postoperative condition. 5,[7][8][9][14][15][16] Exclusion criteria: patients age <65 years and incomplete data were excluded from the study.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation